New data on the genus Opilio Herbst, 1798 (Arachnida, Opiliones) in Azerbaijan Republic including a description of two new species - Snegovaya, N.y. (Zootaxa, 2026)
Two new opilionid species of the family Phalangiidae, Opilio zuvandicus sp. nov. and Opilio zangezuricus sp. nov. are diagnosed, illustrated and described on the basis of morphological methods from the territory of the Lerik and Kelbajar discticts of the Azerbaijan Republic. The described species are characterized by large body sizes and long thin legs, wide wings in the distal part of the penis.